Tradisi Orientalisme dan Framework Studi al-Qur’an - Hamid Fahmy Zarkasyi (Universitas Darussalam Gontor, 2011)
Orientalism is a field of study that deals with Eastern and Islamic studies as it object of study. Being a discipline of knowledge it must have specific theory and methodology or framework of study. However, since it emerged in Western intellectual tradition, it is permeated by Western worldview. In other words, being a science orientalism is value laden. This paper tries to prove the correlation between the traditions of orientalism, where religious, cultural and political melieu permeated their framework, with the study of the Qur’an. The finding suggests that the framework of orientalis in their study of the Qur’an could be resumed into four: trying to employ previous sacred text as their standard of Qur’anic studies, preferring the textual studies rather than narration, questioning the process of compilation, examining the content of the Qur’an using their own logic and experience, and finally employing the Biblical methodology. Those frameworks inevitably has resulted incongruencies that could lead one to be misunderstanding the Qur’an